2018
DOI: 10.1128/mra.01416-18
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli NGF-1, a Genetically Tractable, Efficiently Colonizing Murine Gut Isolate

Abstract: The genome of the murine commensal strain Escherichia coli NGF-1 contains a 5.03-Mbp chromosome and plasmids of 40.2 kbp and 8.56 kbp. NGF-1 efficiently colonizes the mouse gut and is genetically tractable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…E. coli NGF-1 is a strain originally isolated from the murine gut, which has proven to be an efficient and persistent colonizer and a reliable platform for the deployment of engineered circuits (3, 12, 16). When grown in the presence of a high concentration (100 ng/ml) of anhydrotetracycline (aTc) inducer, cI DN - triggered strains showed switching to the memory-on state, while cro -triggered strains switched only after a subsequent period of growth in the absence of aTc (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…E. coli NGF-1 is a strain originally isolated from the murine gut, which has proven to be an efficient and persistent colonizer and a reliable platform for the deployment of engineered circuits (3, 12, 16). When grown in the presence of a high concentration (100 ng/ml) of anhydrotetracycline (aTc) inducer, cI DN - triggered strains showed switching to the memory-on state, while cro -triggered strains switched only after a subsequent period of growth in the absence of aTc (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Escherichia coli NGF-1 was originally isolated from BALB/c mice, has been shown to stably colonize the mouse gut, and can be engineered with standard genetic tools (2830). Salmonella enterica serovar Typhimurium LT2 ( S. Typhimurium), an attenuated gut pathogen, was rendered further harmless by removing the pathogenicity islands SPI1 and SPI2 and thus causes no disease when administered to mice (31).…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies of an E. coli strain isolated from mouse fecal samples from a different facility (i.e., NGF-1) (Lasaro et al, 2014;Ziesack et al, 2018) likewise demonstrated long-term colonization (Riglar et al, 2017). However, it was not clear whether undomesticated E. coli strains could be used to study specific bacterial functions, affect the luminal environment, and shape host physiology.…”
Section: Discussionmentioning
confidence: 99%